Electrolytic manganese residue-based active cementing material and preparation method thereof

The active gelling materials are prepared by electrolytic manganese slag, red mud and calcium carbide slag at high temperature calcination, which solves the problems of poor activity and difficulty in resource utilization of electrolytic manganese slag, and realizes efficient resource utilization and low-cost manganese Slag treatment meets the performance requirements of S75 slag powder.

CN119263658APending Publication Date: 2025-01-07XIANGTAN UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411603754.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the prior art, the activity of electrolytic manganese slag active gelling materials is poor, and additional excitation or chemical reagents are required, resulting in high cost and insufficient performance, and low resource utilization of manganese ions in manganese slag leaching liquid and slag field leachate. Severe pollution, low recycling rate of water resources, and manganese slag is difficult to be used on a large scale.

Method used

The active gelling materials are prepared by using solid waste materials such as electrolytic manganese slag, red mud and calcium carbide slag at high temperature calcination at 1080-1180°C. Fe2O3 in the red mud is used as an iron-based modifier and active alkali ingredient, and calcium carbide slag is used as a calcium-based additive. Adjust the calcium-silicon ratio and remove residual ammonia (ammonium), red mud and calcium carbide slag are combined with electrolytic manganese slag for high-temperature calcination to promote calcium sulfate decomposition, improve the generation of active calcium oxide, and improve the performance of active gelling materials.

Benefits of technology

The resource utilization of electrolytic manganese slag has been realized, the amount of cement is reduced, the activity index and flow of active cementitious materials have been improved, and the granulated blast furnace slag powder in cement, mortar and concrete is met. The requirements of S75 slag powder reduce treatment costs and the lowest risk of environmental pollution, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263658A_ABST
    Figure CN119263658A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolytic manganese residue-based active cementing material and a preparation method thereof, and belongs to the technical field of solid waste resource utilization. Raw materials including electrolytic manganese residues, red mud and carbide slag are dried, crushed and evenly mixed and then calcined at the temperature of 1080-1180 DEG C, a calcined product is cooled and ground, and the electrolytic manganese residue-based active cementing material is obtained. The preparation process of the electrolytic manganese residue-based active cementing material meets the requirements specified by the HJ 1241-2022 Technical Specification for Manganese Slag Pollution Control. The performance of the obtained cementing material product meets the requirements of GB / T 18046-2017 Granulated Blast Furnace Slag Powder Used in Cement, Mortar and Concrete S75 slag powder, and the cementing material can replace part of cement to be used in concrete, so that efficient resource utilization of solid wastes such as electrolytic manganese residues and the like is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an active gelling material, in particular to an active gelling material prepared from industrial solid wastes such as electrolytic manganese slag, red mud, carbide slag, etc., and also to a preparation method thereof, belonging to the technical field of solid waste resource utilization. Background Art

[0002] Electrolytic manganese is an important raw material for metallurgy and chemical industry, and is widely used in steel industry, chemical industry, light industry, building materials industry, national defense industry, electronic industry, environmental protection and agriculture and animal husbandry. The demand of electrolytic manganese market has promoted the rapid development of electrolytic manganese industry. In response to major issues such as large stockpiles of electrolytic manganese slag, environmental pollution and difficulty in clean utilization, some researchers have carried out research on ammonia-nitrogen wastewater treatment of manganese slag leachate, utilization of manganese slag as building materials through high-temperature sintering, and environmental risk assessment of manganese slag depots. Certain progress has been made, but there are still many problems to be solved. For example, the multiple mineral phases in manganese slag are tightly wrapped and coexist, which makes it impossible to deeply leach resource-attribute elements such as manganese in the slag, resulting in serious waste of resources. The resource utilization rate of manganese ions, ammonia (ammonium) and magnesium ions in the manganese slag leachate and the slag yard leachate is low, causing serious environmental pollution. At the same time, it is difficult to deeply purify sewage from different sources, resulting in a low recycling rate of water resources. The deaminated manganese slag produced after the manganese slag is treated by the leaching process has a high silicon-calcium ratio, which has a significant adverse effect on the quality of subsequent resource products, making it difficult to utilize the manganese slag on a large scale. The soil in the manganese slag yard is very sticky and has high heavy metal and sulfur contents, making it difficult to restore the ecological function of the slag yard.

[0003] The literature ("Preparation and Performance Research of Active Cementitious Materials Based on Electrolytic Manganese Slag", Chen Xi et al., China ENFI Engineering Technology Co., Ltd., 2024) discloses that active cementitious materials were prepared by using electrolytic manganese slag, desulfurization manganese slag and reduction iron-manganese slag, and compared the activity index. The results show that the activity of electrolytic manganese is poor and it is impossible to reach the S75 grade slag powder standard through physical and chemical excitation methods; desulfurization manganese slag can meet the requirements of S75 slag powder after increasing the specific surface area or adding an activator for mixing and grinding; reduction iron-manganese slag has good activity and can be directly used in cement admixtures and other building materials after grinding. The document ("Preparation of electrolytic manganese residue–ground granulated blastfurnace slag cement", Wang et al., Central South University, 2013) discloses adding electrolytic manganese slag as an activator to granulated blast furnace slag powder to prepare electrolytic manganese slag-granulated blast furnace slag powder cement. The study shows that when EMR / Ca(OH)2 / cement is mixed at a weight ratio of 30:3:5, the prepared active cementitious material has the best effect, and its performance exceeds that of P·S 32.5 cement and is close to that of P·S 42.5 cement. However, there are still many problems with the existing technology. Under high-temperature calcination, the active cementitious material prepared only from electrolytic manganese slag has poor activity and needs to be stimulated by physical methods or the addition of chemical reagents. There are problems such as high reagent cost and insufficient performance of active cementitious materials. Summary of the invention

[0005] In view of the technical problems existing in the prior art, the first object of the present invention is to provide an electrolytic manganese slag-based active cementitious material, the performance of which meets the requirements of S75 slag powder in GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete", and can be used as an active admixture to replace cement in concrete, so as to reduce the amount of cement used and realize the resource utilization of electrolytic manganese slag.

[0006] The second object of the present invention is to provide a method for preparing an electrolytic manganese slag-based active cementitious material. The raw materials of the method are all solid waste, with high solid waste utilization rate and low cost, and only one-step high-temperature calcination is required, and the operation is simple. The deaminated manganese slag produced after the leaching process has a high silicon-calcium ratio, which has a great adverse effect on the quality of subsequent resource products, resulting in the problem that manganese slag is difficult to be utilized on a large scale. The process of preparing the electrolytic manganese slag active cementitious material meets the requirements specified in HJ 1241-2022 "Technical Specifications for Manganese Slag Pollution Control", and the performance of the obtained electrolytic manganese slag active cementitious material product meets the requirements of S75 slag powder in GB / T 18046-2017 "Granulated blast furnace slag powder used in cement, mortar and concrete".

[0007] In order to achieve the above technical purpose, the present invention provides an electrolytic manganese slag-based active gelling material, which is obtained by calcining the following raw materials at a high temperature of 1080-1180°C; the raw materials include electrolytic manganese slag, red mud and carbide slag.

[0008] The electrolytic manganese slag-based active gelling material of the present invention uses raw materials such as electrolytic manganese slag, red mud and carbide slag, which are all solid waste materials, and obtains high-value-added active gelling materials, which truly realizes the resource utilization of solid waste resources. The electrolytic manganese slag-based active gelling material fully utilizes the synergistic effect between the components contained in the raw materials themselves, and no additional components need to be added: due to the low calcium-silicon ratio (only 0.64) and high content of components such as ammonia (ammonium) sulfur in the manganese slag, the deammonated manganese slag has low activity after high-temperature calcination, difficulty in separating and recovering nitrogen oxides and sulfur dioxide, and poor performance of the active gelling material, which makes it difficult to process and utilize resources on a large scale. Considering that the main chemical component of carbide slag is CaO (67.87%), it can be used as a calcium-based additive to optimize the alkalinity structure of the mixed material, promote the removal of residual ammonia (ammonium) in the electrolytic manganese slag during the calcination process, and adjust the calcium-silicon ratio of the raw material to overcome the defect of low calcium-silicon ratio (only 0.64) of the electrolytic manganese slag; but if only carbide slag is added, the active cementitious material prepared after calcining the electrolytic manganese slag still has the problem of excessively high mass fraction of sulfur trioxide (mainly in the form of CaSO4), resulting in insufficient performance of the active cementitious material. Therefore, a modifier is still needed to solve this problem. Considering that one of the main chemical components in red mud is Fe2O3 (44.7%), it can be used as an iron-based modifier to promote the decomposition of calcium sulfate in the electrolytic manganese slag at a high temperature stage, realize the desulfurization of the electrolytic manganese slag, and produce highly active calcium oxide. At the same time, red mud also contains a large amount of active alkali components, which can be used as an activator component. Therefore, high-temperature calcination of red mud and carbide slag with electrolytic manganese slag can greatly improve the gelling activity of electrolytic manganese slag, effectively solving the technical problems of high silicon-calcium ratio, high content of ammonia (ammonium) sulfur and other components in the manganese slag leaching slag, which makes it difficult to treat manganese slag as a resource on a large scale, high treatment cost and low product quality.

[0009] As a preferred solution, the raw materials are composed of the following mass percentage components: 55% to 60% electrolytic manganese slag, 15% to 20% red mud, and 20% to 30% carbide slag. The raw materials of each component in the electrolytic manganese slag-based active cementitious material of the present invention are compounded according to the above preferred ratio requirements, and the product performance can reach the requirements of S75 slag powder in GB / T18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete". If the carbide slag content in the raw materials is less than 20%, the activity index of the electrolytic manganese slag-based active cementitious material after calcination will be too low, and it will not be able to meet the requirements of 7d activity index of 55% and 28d activity index of 75% required by S75 slag powder in GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete". Therefore, the preferred mass percentage of carbide slag is 20% to 30%. If the red mud content in the raw material is less than 15%, it is difficult to promote the deep removal of sulfur in the electrolytic manganese slag, which will result in too high a residual amount of heavy SO3 in the electrolytic manganese slag after calcination, and cannot meet the requirements of S75 slag powder ≤4.0% and fluidity ratio ≥95% in GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete". Therefore, the mass percentage of red mud is preferably 15% to 20%. Excessive content of red mud and carbide slag will affect the consumption of electrolytic manganese slag, and will also cause a decrease in the content of active cementitious ingredients. The three are matched in appropriate proportions, so that the active cementitious material can meet the requirements of S75 slag powder in GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete".

[0010] The present invention also provides a method for preparing an electrolytic manganese slag-based active gelling material, which comprises drying, crushing and mixing raw materials including electrolytic manganese slag, red mud and carbide slag, calcining them at a temperature of 1080-1180°C, and cooling and grinding the calcined products to obtain the active gelling material.

[0011] The key to the electrolytic manganese slag-based active cementitious material of the present invention is to calcine the mixture of electrolytic manganese slag, red mud and carbide slag at a high temperature of 1080-1180°C, and make full use of the red mud and carbide slag to react with the components contained in the electrolytic manganese slag at a high temperature to achieve deep deamination (ammonium) and sulfur removal of the electrolytic manganese slag, while improving the gelling activity of the electrolytic manganese slag. If the calcination temperature is too low, the electrolytic manganese slag will not be fully activated, and its activity index will be low, and the sulfur will not be deeply removed, which will not meet the requirements of S75 slag powder in GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete". If the temperature is too high, the energy consumption will be too high, and sintering and agglomeration will occur. Under the conditions of optimizing the raw material composition of electrolytic manganese slag, red mud and carbide slag and optimizing the calcination temperature, the obtained active cementitious material meets the density ≥2.8g / cm 3, activity index 7d ≥ 55%, 28d ≥ 75%, fluidity ratio ≥ 95%, water content (mass fraction) ≤ 1.0%, sulfur trioxide (mass fraction) ≤ 4.0%.

[0012] As a preferred solution, the drying conditions are: temperature of 100-110°C, time of 12-36 hours. The drying conditions are further preferably: temperature of 105°C, time of 24 hours.

[0013] As a preferred solution, the crushing adopts a universal crusher crushing method, and the crushing conditions are: a rotation speed of 20000-25000r / min, and a time of 2-10min. The crushing to the particle size meets -80 mesh (-80 mesh is a conventional term in the industry, i.e., the undersize of the 80 mesh sieve) is beneficial to the subsequent high-temperature solid phase reaction process.

[0014] As a preferred solution, the mixing is carried out by stirring and mixing, and the stirring and mixing conditions are: a stirring rate of 15000 to 22000 r / min and a time of 10 to 20 min.

[0015] As a preferred solution, the calcination conditions are: heating to 1080-1180° C. at a rate of 5-15° C. / min, and the calcination time is 30-60 min.

[0016] As a preferred solution, the grinding is to meet the particle size of -200 mesh.

[0017] Compared with the prior art, the beneficial technical effects brought by the present invention are as follows:

[0018] 1) The raw materials of the electrolytic manganese slag-based active cementitious material provided by the present invention are all solid waste materials, and the raw material sources are wide, the processing method is simple, and the processing cost is low. By utilizing the synergistic effect between the raw material components, the main chemical component CaO of the calcium carbide slag can be used as a calcium-based additive to optimize the alkalinity structure of the mixed material and change the calcium-silicon ratio of the raw material. The main chemical component Fe2O3 of the red mud can be used as a modifier to further promote the removal of residual ammonia (ammonium) in the low-temperature stage, realize the early volatilization and recovery of ammonia (ammonium) in the electrolytic manganese slag, and promote the decomposition of calcium sulfate in the high-temperature stage, thereby improving the product quality while ensuring the process stability and product quality of high-temperature sintering flue gas desulfurization and acid production, which is beneficial to the enrichment and recovery of tail gas sulfur dioxide to achieve the purpose of reducing costs for subsequent use in building materials.

[0019] 2) The preparation method of the electrolytic manganese slag-based active gelling material provided by the present invention has the characteristics of simple and mature process, and the environmental pollution risk is the lowest among the various manganese slag treatment methods currently used, thereby realizing the resource treatment of solid waste materials.

[0020] 3) The electrolytic manganese slag-based active cementitious material provided by the present invention can have an electrolytic manganese slag content of more than 55%, and its performance meets the requirements of S75 slag powder in GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete", and is suitable for large-scale, continuous and industrialized production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the XRD diagram of electrolytic manganese slag-based active cementitious material. DETAILED DESCRIPTION

[0023] In order for those skilled in the art to better understand the present invention, the present invention is further described in detail below in conjunction with the following embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention.

[0024] The preparation method of the electrolytic manganese slag-based active gelling material in the following examples is as follows:

[0025] The electrolytic manganese slag, red mud and carbide slag are dried and crushed respectively, mixed and calcined at high temperature, and the calcined products are cooled and ground to obtain electrolytic manganese slag-based active gelling materials. Among them, the drying of electrolytic manganese slag, red mud and carbide slag adopts oven drying, and the drying conditions are temperature of 105°C and time of 24h. The crushing of electrolytic manganese slag, red mud and carbide slag adopts universal crushing method, and the conditions of universal crushing are: speed of 20000-25000r / min, time of 5min, crushing to particle size of 80 mesh. The mixing of electrolytic manganese slag, red mud and carbide slag adopts universal crushing method, and the stirring and mixing conditions are 15000-22000r / min and time of 15min. The high-temperature calcination of electrolytic manganese slag, red mud and carbide slag adopts the conditions of heating to 1100°C at a rate of 10°C / min and roasting time of 45min.

[0026] Example 1

[0027] The mass percentages of the raw material components in this embodiment are as follows: 60% of electrolytic manganese slag, 18% of red mud, and 22% of carbide slag.

[0028] Table 1 Chemical composition of each raw material

[0029]

[0030] The preparation process steps are as follows:

[0031] a.Put the electrolytic manganese slag, carbide slag and red mud in a 105℃ oven and dry for 24 hours, take out the electrolytic manganese slag and pour it into a crusher for crushing and sieving 80 mesh. Put the carbide slag in a 105℃ oven and dry for 24 hours, take out the carbide slag and pour it into a crusher for crushing and sieving 80 mesh. Put the red mud in a 105℃ oven and dry for 24 hours, take out the red mud and sieve 80 mesh.

[0032] b. Add the sieved electrolytic manganese slag, red mud and carbide slag into the mixer by weight and stir at a speed of 20,000 r / min for 15 min to obtain a mixed raw material.

[0033] c. Take the mixture and heat it to 1100°C at a rate of 10°C / min for high temperature calcination for 45 minutes. Then take it out and cool it to room temperature to obtain an electrolytic manganese slag-based active gelling material.

[0034] d. Grind the electrolytic manganese slag-based active gelling material to a particle size of 200 meshes to obtain a finished product.

[0035] The measured performance of the finished product meets the requirements of S75 slag powder in GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete".

[0036] Table 2 Performance test results of active gelling material in Example 1

[0037]

[0038]

[0039] Example 2

[0040] The difference from Example 1 is that the ratio is 55% electrolytic manganese slag, 15% red mud, and 30% carbide slag. The chemical composition of the raw materials is the same as that of Example 1.

[0041] The preparation steps are shown in Example 1.

[0042] The measured performance of the finished product meets the requirements of S75 slag powder in GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete".

[0043] Table 3 Performance test results of active gelling material in Example 2

[0044]

[0045] Example 3

[0046] The difference from Example 1 is that the ratio is 60% electrolytic manganese slag, 20% red mud, and 20% carbide slag. The chemical composition of the raw materials is the same as that of Example 1.

[0047] The preparation steps are shown in Example 1.

[0048] The measured performance of the finished product meets the requirements of S75 slag powder in GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete".

[0049] Table 4 Performance test results of active gelling material in Example 3

[0050]

[0051] Comparative Example 1

[0052] The difference from Example 1 is that the ratio is 75% electrolytic manganese slag, 0% red mud, and 25% calcium carbide slag. The chemical composition of the raw materials is the same as that of Example 1.

[0053] The preparation steps are shown in Example 1.

[0054] The measured fluidity ratio of the finished product was 87.3% and the mass fraction of sulfur trioxide was 4.02%, which did not meet the requirements for S75 slag powder in GB / T18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete".

[0055] Table 5 Comparative Example 1 Active Cementing Material Performance Test Results

[0056]

[0057]

[0058] Comparative Example 2

[0059] The difference from Example 1 is that the ratio is 75% electrolytic manganese slag, 25% red mud, and 0% carbide slag. The chemical composition of the raw materials is the same as that of Example 1.

[0060] The preparation steps are shown in Example 1.

[0061] The measured 7d activity index of the finished product was 35.16% and the 28d activity index was 52.33%, which did not meet the requirements for S75 slag powder in GB / T18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete".

[0062] Table 6 Comparative Example 2 Active Cementitious Material Performance Test Results

[0063]

[0064] Comparative Example 3

[0065] The difference from Example 1 is that the ratio is 66% electrolytic manganese slag, 20% red mud, and 14% calcium carbide slag. The chemical composition of the raw materials is the same as that of Example 1.

[0066] The preparation steps are shown in Example 1.

[0067] The measured 7d activity index of the finished product was 37.61% and the 28d activity index was 58.19%, which did not meet the requirements for S75 slag powder in GB / T18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete".

[0068] Table 7 Comparative Example 3 Active Cementitious Material Performance Test Results

[0069]

[0070] Comparative Example 4

[0071] The difference from Example 1 is that the ratio is 55% electrolytic manganese slag, 10% red mud, and 35% calcium carbide slag. The chemical composition of the raw materials is the same as that of Example 1.

[0072] The preparation steps are shown in Example 1.

[0073] The measured fluidity ratio of the finished product is 89.9%, which does not meet the requirements of S75 slag powder in GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete".

[0074] Table 8 Comparative Example 4 Active Cementitious Material Performance Test Results

[0075]

[0076]

[0077] Comparative Example 5

[0078] The difference from Example 1 is that the raw material is only electrolytic manganese slag.

[0079] The preparation steps are shown in Example 1.

[0080] The measured 7d activity index of the finished product was 33%, the 28d activity index was 66.55%, the fluidity ratio was 77.4%, and the mass fraction of sulfur trioxide was 4.02%, which did not meet the requirements for S75 slag powder in GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete".

[0081] Table 9 Comparative Example 5 Active Cementing Material Performance Test Results

[0082]

[0083] Comparative Example 6

[0084] The difference from Example 1 is that the calcination temperature is 1000°C.

[0085] The preparation steps are shown in Example 1.

[0086] The measured 7d activity index of the finished product was 29%, the 28d activity index was 38.2%, the fluidity ratio was 66.2%, the mass fraction of sulfur trioxide was 8.03%, and the loss on ignition was 4.7%, which did not meet the requirements for S75 slag powder in GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete".

[0087] Table 10 Comparative Example 6 Active Cementitious Material Performance Test Results

[0088]

[0089] When the content of carbide slag or red mud in the raw materials is too low, or only one of them is added or not added, or the calcination temperature is not enough, the performance of the active cementitious material does not meet the requirements of S75 slag powder in GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete".

[0090] The above embodiments are merely exemplary descriptions of the present invention and do not limit its protection scope. Those skilled in the art may also make partial changes thereto, which are within the protection scope of the present invention as long as they do not exceed the spirit of this patent.

Claims

1. An electrolytic manganese slag-based active gelling material, characterized in that: The raw materials are calcined at 1080-1180°C to obtain the electrolytic manganese slag, red mud and carbide slag.

2. The electrolytic manganese slag-based active gelling material according to claim 1, characterized in that: The raw material consists of the following components in percentage by mass: 55% to 60% of electrolytic manganese slag, 15% to 20% of red mud, and 20% to 30% of carbide slag.

3. The method for preparing an electrolytic manganese slag-based active gelling material according to claim 1 or 2, characterized in that: The raw materials including electrolytic manganese slag, red mud and carbide slag are dried, crushed and mixed, and then calcined at a temperature of 1080-1180°C. The calcined product is cooled and ground to obtain the product.

4. The method for preparing an electrolytic manganese slag-based active gelling material according to claim 3, characterized in that: The drying conditions are: temperature of 100-110° C. and time of 12-36 hours.

5. The method for preparing an electrolytic manganese slag-based active gelling material according to claim 3, characterized in that: The crushing adopts a universal crusher crushing method, and the crushing conditions are: a rotation speed of 20000-25000r / min, and a time of 2-10min.

6. The method for preparing an electrolytic manganese slag-based active gelling material according to claim 3, characterized in that: The mixing is carried out by stirring and mixing, and the stirring and mixing conditions are: a stirring rate of 15000-22000 r / min and a time of 10-20 min.

7. The method for preparing an electrolytic manganese slag-based active gelling material according to claim 3, characterized in that: The calcination conditions are: heating to 1080-1180° C. at a rate of 5-15° C. / min, and calcination time is 30-60 min.

8. The method for preparing an electrolytic manganese slag-based active gelling material according to claim 3, characterized in that: The grinding is to meet the particle size of -200 mesh.